2015
DOI: 10.3109/21678421.2015.1107100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of Russian patients with amyotrophic lateral sclerosis

Abstract: Our objective was to search for mutations in genes SOD1, TARDBP, C9orf72, ANG, ATXN2 and VEGF in Russian patients with amyotrophic lateral sclerosis (ALS). A group of 208 Russian patients with ALS was examined. Molecular genetic analysis was conducted using direct sequencing, fragment analysis, and real-time PCR. We found eight different point mutations in the SOD1 gene, with the frequency of mutations being 50% in familial ALS and 3% in sporadic ALS. No mutations were found in exon 6 of the TARDBP gene; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…2021; 20 (3): 193-202 ций SOD1 наследуются АД [26], однако также описаны случаи с АР типом наследования [27,28]. Частота мутаций SOD1 варьирует от 12 до 23,5% пациентов с сБАС и 5-10% спорадических случаев заболевания [29,30]. В настоящее время описано более 100 мутаций гена SOD1, большинство из которых являются точечными.…”
Section: локус Als1 (ген Sod1)unclassified
“…2021; 20 (3): 193-202 ций SOD1 наследуются АД [26], однако также описаны случаи с АР типом наследования [27,28]. Частота мутаций SOD1 варьирует от 12 до 23,5% пациентов с сБАС и 5-10% спорадических случаев заболевания [29,30]. В настоящее время описано более 100 мутаций гена SOD1, большинство из которых являются точечными.…”
Section: локус Als1 (ген Sod1)unclassified
“…Some genes are not only risk factors, but they may also be survival modifiers. Several studies have shown that UNC13A [3,57,58,] and ATXN2 [59,60,61] are associated with shorter survival in ALS. The type of mutation lying in the TARDBP super rich glycine-residue domain was associated with the worst survival [62 ].…”
Section: Reviewmentioning
confidence: 99%
“…Colorectal cancer is the second cause of cancer death (after breast cancer) in women and the third for men (after lung and stomach cancers), and both the incidence and mortality have increased since 2000 [28]. With respect to neurodegenerative disease, Russian research has focused mainly on genetic risk factors for ALS [29,30]. While Bunina bodies, the neuronal inclusions named for Russian neuropathologist Tat'yana Bunina [31], are seen in familial, sporadic and Guam cases of ALS [32], the epidemiology of ALS in the Russian Federation is not well developed [1].…”
mentioning
confidence: 99%